Total Power and Low-energy Cutoff Time Evolution of Solar Flare Accelerated Electrons Using X-Ray Observations and Warm-target Model - Debesh Bhattacharjee; Eduard P. Kontar; Yingjie Luo (The Astrophysical Journal, 2025)
A primary characteristic of solar flares is the efficient acceleration of electrons to nonthermal deka-keV energies. While hard X-ray (HXR) observation of bremsstrahlung emission serves as the key diagnostic of these electrons. In this study, we investigate the time evolution of flare-accelerated electrons using the warm-target model. This model, unlike the commonly used cold-target model, can determine the low-energy cutoff in the nonthermal electron distribution, so that the energetics of nonthermal electrons can be deduced more accurately. Here, we examine the time-evolution of nonthermal electrons in flares well-observed by the Reuven Ramaty High Resolution Solar Spectroscopic Imager and the Solar Orbiter spacecraft (using the Spectrometer/Telescope for Imaging X-rays instrument). Using spectroscopic and imaging HXR observations, the time evolution of the low-energy cutoff of the accelerated electron distribution, the total power of nonthermal electrons, total rate of nonthermal electrons, and excess thermal emission measure from the nonthermal electrons are investigated. We find that the time profile of the low-energy cutoff of the accelerated electron distribution shows a high-low-high trend around the HXR bursts of flares, while the time evolution of the total rate of injected electrons shows a low-high-low behavior. Although the total power of nonthermal electrons is sensitive to the cutoff energy, the temporal variation of the flare power follows the temporal variation of the acceleration rate. We further find that the highest contribution of the excess thermal emission measure coming from thermalization of injected electrons takes place around the HXR peak.